The Effect of Storytelling Therapy Before Sleep in Sleep Quality Preschool Age Children Undergoing Hospitalization in the Child Care Room Sanglah Hospital Denpasar - Ni Putu Eka Yuniartini (Coping: Community of Publishing in Nursing, 2013)
The hospitalization in children will bring some changes in the psychological tension and anxiety that affects to the child sleep quality disturbance. The therapy that can we do to decreasing the psychological tension is storytelling. The aim of study is to analyze the influence of storytelling therapy in sleep quality to preschool age children who are undergoing hospitalization. This research is a pre-experimental study (pre-test and post-test without control group design). The population in this study amounted to 35 people and the sample used amounted to 21 people. Method of sampling in this study is the non probability sampling with consecutive sampling technique. The data was collected using a questionnaire interview and observation of The Children's Sleep Habits Questionnaire (CSHQ) which has been tested the validity and reability. The sleep quality score before conducting storytelling therapy is 21 as much eight respondents (38,1%), with the average score obtained 21,48, the lowest score is 19, and the highest score is 25. After being storytelling therapy, it present that most respondents have sleep quality score as much 28 as much as seven respondents (33.3%), with the average score obtained 28,67, the lowest score was 25, and the highest score is 33. After analyzing by Wilcoxon test, obtained asymp sig value (2-tailed) < ? (0,000 < 0,05), then Ho is rejected, its meaning that there is the influence of storytelling therapy before sleep in sleep quality to preschool age children undergoing hospitalization. Based on the results of this study, it is suggested to the nurse to using storytelling therapy to improve sleep quality of children during hospitalization.